Inter-Annual Variability of Winter Precipitation Over Nepal Coupled With Ocean-Atmospheric Patterns During 1987–2015 - Hamal, Kalpana; Sharma, Shankar; Baniya, Binod; Khadka, Nitesh; Zhou, Xu (Frontiers in Earth Science, 2020)
Nepal is a mountainous country located on the southern slope of the central Himalayas, where ~3% of the total annual rainfall occurs in the winter season. The inter-annual variability and shift in the winter precipitation are of great importance in space and time, however, has not been investigated in Nepal. This study sought to investigate the inter-annual variability of winter precipitation (DJF), below- and above-average winter precipitation anomalies over Nepal and their controlling factors associated with ocean-atmospheric circulation patterns during the historical period of 1987–2015. Here, we used Asian Precipitation-Highly Resolved Observational Data Integration towards Evaluation of Water Resources (APHRODITE), Climate Prediction Center (CPC) database of National Centres for Environmental Prediction (NCEP) and Japan Marine Science and Technology Centre (JAMSTEC) data from different sources to study the Empirical Orthogonal Function (EOF), Wavelet, Composite, and Correlation analysis, respectively. The results show that the leading EOF mode captures 62.1% of the total variance of precipitation exhibiting a single mode of variability. As determined by wavelet analysis, the winter precipitation of Nepal shows 2 to 2.6 year’s power spectrum for 29 years (1987–2015). The time series of winter precipitation anomalies revealed the years 1996, 1998, 2000, 2005, 2007, and 2008 as precipitation deficit years which is supported by the composite analysis showing negative precipitation anomalies with positive outgoing longwave radiation (OLR) and vertical velocity. These phenomena are converse for wet events during 1988, 1995, 1997, 2002, 2012, and 2014. The wet years exhibit moisture convergence with strong south-westerly wind anomalies originated from the Arabian Sea. The dry events reveal moisture divergence with weaker north-westerly wind anomalies. The temperature gradient over Tibetan Plateau is linked with a shift in precipitation regime over Nepal. The further finding indicates that preceding summer monsoon (JJAS) and post-monsoon (ON) warming over the Indo-Pacific Ocean influences the following year's winter precipitation over Nepal. The observed changes in the dry and wet years during winter are useful for disaster preparedness and the planning and monitoring of water resources and agriculture.